2011
DOI: 10.1002/aur.208
|View full text |Cite
|
Sign up to set email alerts
|

Autism and cancer risk

Abstract: A literature review was conducted on the genetic and developmental bases of autism in relation to genes and pathways associated with cancer risk. Convergent lines of evidence from four types of analysis: (1) recent theoretical studies on the causes of autism, (2) epidemiological studies, (3) genetic analyses linking autism with mutations in tumor suppressor genes and other cancer-associated genes and pathways, and (4) contrasts with schizophrenia, Parkinson's, and Alzheimer's disease indicate that autism may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 124 publications
(146 reference statements)
2
47
0
Order By: Relevance
“…Obesity increases the risk for many chronic diseases including diabetes, cardiovascular disease, and cancer (Guh, Zhang et al 2009), and in our study population, adults with ASD did have elevated rates of diabetes, hypertension, and dyslipidemia, but marginally lower rates of cancer. A recent review of the genetic and developmental bases of autism in relation to genes and pathways associated with cancer risk concluded that cancer risk may be altered in autism (Crespi 2011). Further epidemiologic research in large populations is needed to elucidate the association between autism and chronic conditions including cancer and identify explanatory factors for our observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases the risk for many chronic diseases including diabetes, cardiovascular disease, and cancer (Guh, Zhang et al 2009), and in our study population, adults with ASD did have elevated rates of diabetes, hypertension, and dyslipidemia, but marginally lower rates of cancer. A recent review of the genetic and developmental bases of autism in relation to genes and pathways associated with cancer risk concluded that cancer risk may be altered in autism (Crespi 2011). Further epidemiologic research in large populations is needed to elucidate the association between autism and chronic conditions including cancer and identify explanatory factors for our observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…30 The genetic deficits of tuberous sclerosis have been found to be associated with signal transduction to regulate cell growth and survival. 31 The etiology of tuberous sclerosis is mutations in either TSC1 or TSC2 genes. These are tumor-suppressor genes, and their gene products form a heterodimer, the TSC1-TSC2 complex, to regulate as the sensor and integrator of cell growth, and lead to the formation of hamartomas in multiple organs, including brain, kidney, skin, and lung.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to occur due to the genetic and molecular connections between cancer and these complex human diseases (Tabares-Seisdedos et al, 2011). Of greater concern, is a higher incidence of certain cancers in patients with ASD (Crespi, 2011). This is likewise due to shared molecular pathways (Crespi, 2011), and ASD also shares genetic connections with SCZ and Alzheimer disease (Crespi et al, 2010;Sokol et al, 2011).…”
Section: Cancer and Neurological Disordersmentioning
confidence: 99%
“…Of greater concern, is a higher incidence of certain cancers in patients with ASD (Crespi, 2011). This is likewise due to shared molecular pathways (Crespi, 2011), and ASD also shares genetic connections with SCZ and Alzheimer disease (Crespi et al, 2010;Sokol et al, 2011). Indeed, some lines of evidence suggest that ASD and SCZ involve diametric etiology (Crespi et al, 2010).…”
Section: Cancer and Neurological Disordersmentioning
confidence: 99%